PENINGKATAN KEMAMPUAN MENULIS TEKS DESKRIPSI DENGAN MEDIA GAMBAR BERSAMBUNG - Budiyono, Budiyono (UNIB Press, 2016)
The objective of this research was to know the improvement of students’ ability in writing descriptive text by using picture series media. The subject of the research was students on class H at VII (seven) Junior High School 19 Bengkulu City, there were 23 students. The form of this research was a classroom action research. The data of this research were gathered from the descriptive writing test and analyzed by using descriptive analysis. The result showed that there are an improvement of students’ ability in writing descriptive text by using picture series media on class H at VII (seven) Junior High School 19 Bengkulu City. It can be seen from the writing result on cycle I that students’ average score 70 (enough) and increased with 76,04 (good) after repaired on cycle II, then increased again after repaired on cycle III with 86,17 (very good).